Grain refinement in laser powder bed fusion: The influence of dynamic recrystallization and recovery. (November 2020) - Sabzi, Hossein Eskandari; Aboulkhair, Nesma T.; Liang, Xingzhong; Li, Xiao-Hui; Simonelli, Marco; Fu, Hanwei; Rivera-Díaz-del-Castillo, Pedro E.J.
Abstract: During laser powder bed fusion (LPBF) the powder bed undergoes several thermal cycles incorporating complex thermo-mechanical processing. Different restoration mechanisms such as dynamic recovery, dynamic recrystallization and grain growth can be activated at different thermal cycles, leading to a very fine average grain size. This is modelled via classical and thermostatistical approaches for an austenitic stainless steel. Four subsequent thermal cycles in each layer induce various microstructural transitions for each individual grain. The high cooling rate solidification in the first two thermal cycles leads to the formation of a highly deformed cellular microstructure. Discontinuous and continuous dynamic recrystallization are activated in the third thermal cycle to induce grain refinement. The fourth thermal cycle undergoes dynamic recovery and grain growth. The as-built alloys exhibit an excellent combination of high yield and ultimate tensile strength. The high strength is attributed to the activation of the various dynamic recrystallization mechanisms, as well as to the development of the cellular structures resulting from a high cooling rate upon solidification. A methodology to design alloys with tailored microstructures is presented. Graphical abstract: Unlabelled Image Highlights: Detailed characterisation of recrystallized laser powder bed fusion 316L structure Dynamic recrystallization is essential to promote grain refinement in 316L. A methodology for tailoring grain refinement via recrystallization is suggested. Zener-Hollomon and thermostatistical approaches described grain refinement features.